2017
DOI: 10.1371/journal.pone.0176892
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative assessment of climate-driven ecological shifts in the Caspian Sea

Abstract: The worldwide occurrence of complex climate-induced ecological shifts in marine systems is one of the major challenges in sustainable bio-resources management. The occurrence of ecological environment-driven shifts was studied in the Southern Caspian Sea using the “shiftogram” method on available fisheries-related (i.e. commercially important bentho-pelagic fish stocks) ecological and climatic variables. As indicators of potential environmentally driven shift patterns we used indices for the North Atlantic Osc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 60 publications
2
5
1
Order By: Relevance
“…There are even fewer studies on the effect of the EAWR teleconnection pattern on phytoplankton productivity. For example, an attempt was made to link the shift regime in the ecosystem of the Caspian Sea, which occurred in the late 1990s and mid-2000s with changes in the EAWR index, but statistically reliable results could not be obtained (Kashkooli et al, 2017). In our study, we also could not have obtained statistically significant correlations between phytoplankton productivity indicators in the Neva Estuary and EAWR teleconnection pattern (Table 2).…”
Section: Discussioncontrasting
confidence: 58%
See 3 more Smart Citations
“…There are even fewer studies on the effect of the EAWR teleconnection pattern on phytoplankton productivity. For example, an attempt was made to link the shift regime in the ecosystem of the Caspian Sea, which occurred in the late 1990s and mid-2000s with changes in the EAWR index, but statistically reliable results could not be obtained (Kashkooli et al, 2017). In our study, we also could not have obtained statistically significant correlations between phytoplankton productivity indicators in the Neva Estuary and EAWR teleconnection pattern (Table 2).…”
Section: Discussioncontrasting
confidence: 58%
“…The impact of climate variability on marine and estuarine ecosystem has been extensively discussed in recent decades (e.g., Stenseth et al, 2002;Doney, 2006;Doney et al, 2012;Bogatov and Fedorovskiy, 2016;Le et al, 2019;Golubkov and Golubkov, 2020). Climate fluctuations are exogenous and hidden driving forces that are causing profound large-scale changes in marine ecosystems, affecting the state of their environment and biotic interactions on interannual and longer time scales (Andersen et al, 2011;Doney et al, 2012;Kashkooli et al, 2017;Golubkov, 2021). For instance, interannual fluctuations in air temperature and atmospheric precipitation lead to a change in the runoff of nutrients into the Baltic Sea from the catchment area, as well as to alterations in the composition and productivity of phytoplankton (Kotta et al, 2009;Teutschbein et al, 2017;Golubkov and Golubkov, 2020;Golubkov et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This function is an estimate of the association between two variables (CPUE and the physical environmental variables) at the significant temporal leads and lags (George et al 2005). Temporal lags in the relationship between predictors and the response variable were accounted for, because it has been reported that climate indices influence recruitment success of fish species several months and even years later (Kashkooli et al 2017). Positive time lags represent a positive correlation between driver and response and could indicate causality.…”
Section: Methodsmentioning
confidence: 99%